Mathematics and Computation in Music 4th International Conference, MCM 2013, Montreal, QC, Canada, June 12-14, 2013. Proceedings - Yust, Jason.; Wild, Jonathan.; Burgoyne, John Ashley. (Lecture Notes in Computer Science,, 2013)
This book constitutes the thoroughly refereed proceedings of the Fourth International Conference on Mathematics and Computation in Music, MCM 2013, held in Montreal, Canada, in June 2013. The 18 papers presented were carefully reviewed and selected from numerous submissions. They are promoting the collaboration and exchange of ideas among researchers in music theory, mathematics, computer science, musicology, cognition and other related fields.